Origin and Attribution of the Items in Eastern European Champlevé Enamels Style (Late 2nd – 4th Centuries) Found South-Eastward of the Main Dnieper Area - Oleg A. Radyush (Нижневолжский археологический вестник)
This article examines the origin and attribution of ornaments in Eastern European style found to the south and east of the main Dnieper area of such artifacts. Previously unknown artifacts are introduced into scientific circulation. Development of local barbarian jewelry styles in Eastern Europe reached its peak in the late 2nd – mid-3rd centuries AD. Most known enameled finds belong to this time period, although some types of items can be traced back to the late 4th to early 5th centuries. Archaeological finds from closed complexes in the Northwestern Black Sea region, the Crimea, the North Caucasus, and the Lower Don are dated to all stages of the enameled style development. The early stage includes such sites as Bedrazhy Noi and Krasny Mayak, while the middle stage is represented by Valovyi I, Kepy, Chatyr-Dag, Diviziya, Skalistoye (burial 28Л), and Neapolis-Scythian. The late stage of development can be attributed to Neyzats (graves 275 and 480). Numerous casual finds in the Crimea area suggest regular connections between the northern forest-steppe and forest territories with the peninsula from early forms to later varieties of enameled items. The article discusses issues of ethno-cultural attribution and distribution of the enameled ornaments. Various theories and hypotheses about the origin of enamels associate them with different ethnic groups and regions. The movement of groups from the Dnieper region eastward through the Central Don and Khoper formed contacts with the local population reaching as far as the Volga region. However, the Caucasian finds, due to their remoteness and specific context, are of particular interest. Military campaigns along the Black Sea coast and the involvement of numerous tribes in those conflicts contributed to the spread of the enamel tradition, as evidenced by finds in the Crimea and the Lower Don region. It is also worth considering various forms of matrimonial contacts, given the fact that many burials were female.